STROBE-AMS: recommendations to optimise reporting of epidemiological studies on antimicrobial resistance and informing improvement in antimicrobial stewardship - Tacconelli, Evelina; Mutters, Nico T. (BMJ open, 2016)
Objectives To explore the accuracy of application of the Strengthening the Reporting of Observational Studies in Epidemiology (STROBE) tool in epidemiological studies focused on the evaluation of the role of antibiotics in selecting resistance, and to derive and test an extension of STROBE to improve the suitability of the tool in evaluating the quality of reporting in these area. - Methods A three-step study was performed. First, a systematic review of the literature analysing the association between antimicrobial exposure and acquisition of methicillin-resistant Staphylococcus aureus and/or multidrug-resistant Acinetobacter baumannii was performed. Second, articles were reviewed according to the STROBE checklist for epidemiological studies. Third, a set of potential new items focused on antimicrobial-resistance quality indicators was derived through an expert two-round RAND-modified Delphi procedure and tested on the articles selected through the literature review. - Results The literature search identified 78 studies. Overall, the quality of reporting appeared to be poor in most areas. Five STROBE items, comprising statistical analysis and study objectives, were satisfactory in <25% of the studies. Informative abstract, reporting of bias, control of confounding, generalisability and description of study size were missing in more than half the articles. A set of 21 new items was developed and tested. The new items focused particularly on the study setting, antimicrobial usage indicators, and patients epidemiological and clinical characteristics. The performance of the new items in included studies was very low (<25%). - Conclusions Our paper reveals that reporting in epidemiological papers analysing the association between antimicrobial usage and development of resistance is poor. The implementation of the newly developed STROBE for antimicrobial stewardship (AMS) tool should enhance appropriate study design and reporting, and therefore contribute to the improvement of evidence to be used for AMS programme development and assessment.
Gesehen am 26.05.2020